YÜKSEKÖĞRETİMDE YABANCI DİL ÖĞRETİMİ VE SORUNLARI (FIRAT ÜNİVERSİTESİ ÖRNEĞİ) - GÖMLEKSİZ, MEHMET NURİ (Fırat Üniveristesi, 1993)
Teaching a foreign language has always been one of the aims of Turkish universities. To reach the standards of developed countries in science, technology, art etc. and to follow new scientific developments in every area are the reasons that make learning a foreign language important and necessary. In addition to these reasons, people need to learn a foreign language to he able to get a good job. There are some problems dealing with foreign language teaching at university level in Türkiye. These are; the level of knowledge the students bring with them to the university, the lack of motivation of the students to learn a foreign language, insufficiency of teaching hours per week, insufficiency of teaching methods the teachers use and the absence of the equipment such as language laboratory, video, tape recorder etc. Large classes are also one of the factors preventing foreign language teaching effectively. One of the steps to be taken to get success in foreign language classes is to change the whole system dealing with foreign language lessons. There should be a preparatory school for the first year. The necessary equipment such as language laboratory, video, tape recorder etc. should be ensured. Teaching hours should be increased. The teachers should use modern teaching methods based on psychological and educational learning theories. Instead of using a single method/it should be preffered to use the suitable sides of every method. Four basic skills (listening, speaking, reading and writing) should be taken into consideration, and equal importance should be given to these skills. Ill
Keywords: Eğitim ve Öğretim; Education and Training